The new Mexican political system: reconfiguration of capacities and power - G. L. Montiel (Ибероамериканские тетради)
There exist different elements that contribute to the idea of the political system as such in the context of the Mexican experience, but also that serve as referents that characterize the recent past. For that reason, we present a scheme of analysis – with political trends that are being built and that differentiate the new Mexican political system compared to that of the 20th century. Based on a model of the political system as the methodology of the analysis, we will track the trends of the changing Mexican politics during the 21st century. The destruction of the institutions of the old political system is associated with a long process of political struggle, which has provided for the creation of new institutions, but in very specific political spaces. The article traces the changes in the political system of Mexico in the 21st century in its various spheres and manifestations: public authority, party system, electoral complex, civil society, the process of democratization. We consider the evolution of the three branches of government and analyze their current balance.